Regional differences in health, diet and weaning patterns amongst the first Neolithic farmers of central Europe - Ash, Abigail; Francken, Michael; Pap, Ildikó; Tvrdý, Zdeněk; Wahl, Joachim; Pinhasi, Ron (Scientific reports, 2016)
Across much of central Europe, the Linearbandkeramik (LBK) represents the first Neolithic communities. Arising in Transdanubia around 5500 cal. BC the LBK spread west to the Rhine within two to three hundred years, carrying elements of a mixed agricultural economy and a relatively homogeneous material culture. Colonisation of new regions during this progress would have required economic adaptations to varied ecological conditions within the landscape. This paper investigates whether such adaptation at a local scale affected health patterns and altered the dietary habits of populations that otherwise shared a common cultural and biological origin. Analysis of non-specific stress (linear enamel hypoplasia, porotic hyperostosis, cribra orbitalia) within five LBK populations from across central Europe in conjunction with published carbon and nitrogen stable isotope data from each site revealed a high prevalence of porotic hyperostosis and cribra orbitalia in western populations that was associated with a lower animal protein intake. Hypoplastic enamel was more frequently observed in eastern populations however, and may reflect geographic differences in childhood morbidity and mortality as a result of variation in social practices relating to weaning. Local socio-economic adaptations within the LBK were therefore an important factor in the exposure of populations to non-specific stress.
Keywords: mitochondriální DNA; Adaptation, Biological; DNA, Mitochondrial; hypoplazie zubní skloviny; stravovací zvyklosti; Health Surveys; hyperostóza; Europe; sociální přizpůsobení; antropologie fyzická; Farmers; archeologie; Body Remains; Dental Enamel Hypoplasia; tělesné pozůstatky; zemědělci; Social Adjustment; Evropa; Animals; Archaeology; zvířata; zdravotnické přehledy; Weaning; Hyperostosis; biologická adaptace; Anthropology, Physical; odstavení; Feeding Behavior